The Role of Natural Gas Exports in Libya GDP during the Period (1988-2018): An Analytical Econometric Study - Qumu, Rabia Bin Arous; Naji, Youssef Abdullah (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study aims to identify the role of natural gas exports in the GDP of the Libyan economy using time series data for the period 1988-2018. Using econometric methods by examining the stability of time series by applying the Dickey- Fuller test, and using the bounds test to detect the presence of joint integration between the study variables and estimate the relationship between them in the long and short term using the autoregressive distributed lag model. The results obtained revealed that there is a causal relationship and an upward trend between natural gas exports in the GDP in the long and short term, and when forecasting for eight years after the study, the strong positive impact of natural gas exports on the GDP was verified. The study suggests that it is necessary to develop the importance of the natural gas industry in Libya, raise production capacity to benefit from the natural gas reserve, provide mechanisms to attract foreign investment to stimulate production work and benefit from expertise and technology to increase for export and thus raise economic growth rates.